Consensus-building around the conceptualisation and implementation of sustainable healthy diets: a foundation for policymakers - Anna Bach-Faig; Kremlin Wickramasinghe; Natalia Panadero; Sergi Fàbregues; Holly Rippin; Afton Halloran; Ujué Fresán; Mary Pattison; João Breda (BMC, 2022)
Abstract Background Healthy and sustainable diets need to be adopted to reduce the negative impact of food consumption on human and planetary health. Food systems account for a third of greenhouse gas emissions. "Dietary Patterns for Health and Sustainability" is a World Health Organization (WHO) project that aims to build consensus among international food, health, and sustainability experts and policymakers on how to conceptualise healthy and sustainable diets and on the actions and policies that could be implemented in the WHO European Region to promote these diets. Methods A qualitative study among European food, health, and sustainability experts and policymakers to elicit their views on multiple dimensions of food sustainability and health was carried out using a three-phase process, including semi-structured interviews, a Nominal Group Technique, and focus groups during a participatory WHO workshop held in Copenhagen. Thematic analysis was used to analyse the three data sources. Results The workshop resulted in a shared understanding of the interconnected components of sustainable healthy eating habits. As a result of this understanding, a variety of potential solutions were identified, including actions across different policy domains, tools, strategic guidelines, needs, and pathways for sustainable healthy diets. The pathways included the need for a multi-stakeholder approach, as well as the simultaneous execution of an aligned and coherent mix of policies at the local and national levels. Conclusions The prioritised actions should be aimed at helping government policymakers promote sustainable healthy diets and make decisions on improving dietary patterns for citizens' health and wellbeing in line with the United Nations Sustainable Development Goals in the European Region.